Noise expectation and house prices - Andreas Mense; Konstantin A. Kholodilin (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
In this paper, we examine the effects of an airport expansion on the prices of houses and flats located under the planned flight corridors. We focus on the role of expectations about the exposure to noise and find that proximity to the planned corridors significantly reduces real estate prices in the affected areas, by around 41% to 60%, depending on the sample. Hereby, the various plans of expanding Berlin-Brandenburg International airport are used as a source of exogenous variation.
Keywords: C21; L93; R31; 330; airport noise; housing prices; price expectations; quasi-experiment; spatial effects